Open-Delta VSC Based Voltage Controller in Isolated Power Systems - Shilpi Bhattacharya; Prabal Deb; Sujit K Biswas; Ambarnath Banerjee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper proposes a reduced switch Open-Delta (OD-VSC) voltage controller for an standalone asynchronous generator (SAG), also known as the self-excited induction generator (SEIG),used in constant power applications such as pico hydro uncontrolled turbine driven isolated induction generator (IAG) for feeding three-phase loads. The proposed reduced switch voltage controller is used to regulate and control the generator terminal voltage as it is subjected to voltage drops, dips or flickers when the isolated power system is subjected to various critical loads. Generally this purpose is carried out by a STATCOM comprising of a three-leg six-switch inverter structure. Here, in this work the DSTATCOM is realized using a three-leg four-switch insulated gate bipolar transistor (IGBT)-based current controlled voltage-sourced converter (CC-VSC) and a self-supporting dc bus containing two split capacitors. The proposed generating system along with the controller is modeled and simulated in MATLAB along with Simulink and power system blockset (PSB) toolboxes. The system is simulated and the capability of the isolated generating system along with the reduced switch based voltage controller is presented here where the generator feeds linear and non-linear loads are investigated.